AN ERROR ANALYSIS ON USING PERSONAL PRONOUNS IN WRITING DESCRIPTIVE TEXT - Rahayu Pratiwi; Rahma Putri Aulia; Lilis Suryani (IKIP Siliwangi, 2019)
The objective of this research was to know the most types of error and the most error of personal pronouns in descriptive text due to the eleventh-grade students in their descriptive paragraph writing. This research conducted qualitative research. This research was conducted at SMK Negeri 1 Cimahi in Academic Year 2018/2019. To get the data, the researchers gave an instruction for the students to make a descriptive text about person, conduct the students' writing result, read the students’ writing result, identified the type of students’ writing error from their text, classified the type of personal pronouns error from students’ writing, and identified the high students, middle students and lower students. The sample of this research is nine students of eleventh grade from PFPT A Class (Broadcast). The result showed that there are four types of errors, they are: omission, addition, misordering, and disordering. In students’ writing had been found many errors that focused on personal pronoun is 8 or 32% of omission error, 0 or 0% of addition error, 17 or 68% of mis-formation error, and 0 or 0% of disordering error. So, the highest percentage of types of error is a mis-formation error that is 17 or 68%. The most error of personal pronouns in descriptive text due by the students is when they used a subject pronoun. Keywords: Error Analysis, Personal Pronoun, Descriptive Text.